2015
DOI: 10.1161/strokeaha.114.008304
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia in Intracerebral Hemorrhage Is Associated With Leukoaraiosis and Hematoma Volume, Not Blood Pressure Reduction

Abstract: Patients with primary ICH and who underwent MRI, including DWI sequences ≤14 days from symptom onset, were included. All known or suspected causes of secondary ICH, such as vascular malformations, structural lesions, trauma, or hemorrhagic transformation of an ischemic infarct, were excluded. The research protocol was approved for waiver of consent by our local Human Research Ethics Board. Blood Pressure AnalysesClinical data and BP data (systolic BP [SBP]/diastolic BP/mean arterial pressure at baseline/1/2/6/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
64
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 26 publications
3
64
0
Order By: Relevance
“…[5][6][7][8][9][10] Over the last several years, a growing number of studies have characterized the presence and frequency of ischemic lesions remote from the acute hematoma visualized on diffusion-weighted imaging (DWI) in patients with primary ICH undergoing MRI. [11][12][13][14][15][16][17][18][19] Across these series, remote DWI lesions are visualized in 11%-41% of patients. There have been conflicting reports of an association between DWI lesions and large fluctuations in BP in the acute hospital setting.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…[5][6][7][8][9][10] Over the last several years, a growing number of studies have characterized the presence and frequency of ischemic lesions remote from the acute hematoma visualized on diffusion-weighted imaging (DWI) in patients with primary ICH undergoing MRI. [11][12][13][14][15][16][17][18][19] Across these series, remote DWI lesions are visualized in 11%-41% of patients. There have been conflicting reports of an association between DWI lesions and large fluctuations in BP in the acute hospital setting.…”
mentioning
confidence: 87%
“…However, the median hematoma volume in our study (9.1 mL) is comparable to the majority of prior MRI-based reports. [12][13][14][15] Of note, the median hematoma volume in the INTERACT II study was 11 mL. 7 MRIs were not all acquired at routine timepoints or with identical magnet strengths and sequence parameters.…”
mentioning
confidence: 99%
“…Previous studies reported PDR in 10-70% of all cases; however, most of these studies were limited by small sample sizes [9][10][11][12][13] . The temporal pattern of ADC properties of the perihematomal zone was previously shown to be highly variable.…”
Section: Discussionmentioning
confidence: 98%
“…This threshold represents a 30% reduction of ADC compared to normal white matter, which is indicative of severely restricted diffusion as reached after prolonged ischemia [16][17][18] . This threshold has previously been used to assess PDR in ICH [10,13] . The ADC of a contralateral mirror ROI was measured as well.…”
Section: Imaging Studiesmentioning
confidence: 99%
See 1 more Smart Citation